Family Self-Efficacy As Caregivers In Caring For Dementia Patients - Audila, Amita; Suharyoto, Suharyoto; Lasman, Lasman; Nurhidayati, Nurhidayati; Purwacaraka, Manggar (Nursing Information Journal, 2025)
Caring for dementia patients is a demanding task requiring physical, emotional, and psychological resilience. Family caregivers' ability to provide optimal care is significantly influenced by their level of self-efficacy. Higher self-efficacy is associated with better caregiving capabilities and lower stress levels. This study aimed to analyze the relationship between self-efficacy and the ability of family caregivers to provide care for dementia patients. Using a quantitative, cross-sectional design, data were collected through the Caregiver Self-Efficacy Scale (CaSES) and caregiving ability from 50 family caregivers. Data analysis involved descriptive statistics and Gamma correlation. The results showed that 50% of caregivers had high self-efficacy, and 48% demonstrated good caregiving abilities. Statistical tests revealed a significant positive relationship between caregiver self-efficacy and caregiving ability (p = 0.006, r = 0.453). Caregivers with higher self-efficacy demonstrated better caregiving skills.